Investigating the use of chatGPT as a tool for enhancing critical thinking and argumentation skills in international relations debates among undergraduate students - Mario de la Puente; Jose Torres; Ana Laura Blanco Troncoso; Yuraima Yuliza Hernández Meza; Jenny Xiomara Marquez Carrascal (Smart Learning Environments)
Abstract This study investigated the effectiveness of using ChatGPT, a large language model (LLM), to enhance critical thinking and argumentation skills among undergraduate students studying international relations in a developing nation context. A total of 95 participants were randomly assigned to an experimental group (n = 48) and a control group (n = 47). The experimental group engaged in debate sessions using ChatGPT, while the control group participated in traditional debate sessions. Pre-test and post-test assessments were conducted to measure the participants’ critical thinking and argumentation skills. The results revealed that the use of ChatGPT significantly improved students' understanding of complex concepts, critical thinking, and argumentation skills compared to traditional debate methods. The findings suggest that integrating LLMs into existing educational curricula may be an effective strategy for enhancing students’ critical thinking and argumentation skills in resource-constrained settings. However, the challenges and limitations associated with the use of LLMs in developing nations should be carefully considered. The study contributes to the growing body of research on the application of AI-powered tools in education and informs the development of evidence-based practices and policies for integrating LLMs into educational curricula.